2020
DOI: 10.3892/etm.2020.8452
|View full text |Cite
|
Sign up to set email alerts
|

Raised CD40L expression attenuates drug resistance in Adriamycin‑resistant THP‑1 cells

Abstract: Acute myeloid leukemia is a common hematological malignancy that often exhibits strong drug resistance when treated using conventional chemotherapy. Although numerous studies have been carried out to develop methods of overcoming drug resistance, the results have generally been unsatisfactory. CD40 ligand (CD40L) has been shown to improve the sensitivity of cancer cells to drug treatment. In the present study, Adriamycin (ADM)-resistant human monocytic THP-1 cells (THP-1/A cells) were developed by incubating T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The suppression of CD40L expression in T cells has also been demonstrated in B cell chronic lymphocytic leukemia ( 14 ). Our previous study demonstrated that the upregulation of CD40L expression attenuated drug resistance in Adriamycin-resistant THP-1 cells ( 15 ). Furthermore, recent studies have demonstrated that CD40L may significantly inhibit the cell proliferation and promote the cell apoptosis of cancer cells, including colon cancer and ovarian cancer cells ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The suppression of CD40L expression in T cells has also been demonstrated in B cell chronic lymphocytic leukemia ( 14 ). Our previous study demonstrated that the upregulation of CD40L expression attenuated drug resistance in Adriamycin-resistant THP-1 cells ( 15 ). Furthermore, recent studies have demonstrated that CD40L may significantly inhibit the cell proliferation and promote the cell apoptosis of cancer cells, including colon cancer and ovarian cancer cells ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%